Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/mt.2011.130
|View full text |Cite
|
Sign up to set email alerts
|

Large-volume Intrathecal Enzyme Delivery Increases Survival of a Mouse Model of Late Infantile Neuronal Ceroid Lipofuscinosis

Abstract: Late infantile neuronal ceroid lipofuscinosis (LINCL) is a progressive neurodegenerative lysosomal storage disorder caused by mutations in TPP1, the gene encoding the lysosomal protease tripeptidyl-peptidase (TPP1). LINCL primarily affects children, is fatal and there is no effective treatment. Administration of recombinant protein has proved effective in treatment of visceral manifestations of other lysosomal storage disorders but to date, only marginal improvement in survival has been obtained for neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 48 publications
4
35
1
Order By: Relevance
“…Recombinant human TPP1 proenzyme was produced in CHO cells and purified as described. 11 For injection, TPP1 was buffer exchanged into phosphate-buffered saline (Gibco) using PD-10 size exclusion columns (GE Healthcare). TPP1 was concentrated using Vivaspin 20 centrifugal concentrators (Sartorius Stedim Biotech, Aubagne, France) to a maximum of 17 mg/ml and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant human TPP1 proenzyme was produced in CHO cells and purified as described. 11 For injection, TPP1 was buffer exchanged into phosphate-buffered saline (Gibco) using PD-10 size exclusion columns (GE Healthcare). TPP1 was concentrated using Vivaspin 20 centrifugal concentrators (Sartorius Stedim Biotech, Aubagne, France) to a maximum of 17 mg/ml and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…One brain hemisphere was drop-fixed in Bouin's reagent and 10 µm sagittal cryosections were processed for TPP1 immunohistochemistry as described. 11 The remaining hemisphere was used to prepare frozen tissue powder using a Bessman pulverizer (Spectrum Laboratories, Rancho Dominguez, CA). For TPP1 enzyme assay, powders were homogenized in 50 volumes (brain, heart, kidney, and lung) or 100 volumes (liver and spleen) of homogenization buffer (0.15 mol/l NaCl /0.1% Triton X-100) using a Polytron homogenizer (Kinematica, Bohemia, NY).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both late infantile CLN2 disease and infantile CLN1 disease share a common defect (soluble lysosomal enzyme deficiency), similar therapeutic strategies might be effective for both. In fact, it has been shown that intracerebroventricular or intrathecal administration of recombinant TPP1 reduces neuroinflammation, decreases the accumulation of autofluorescent material, and improves the clinical course of disease in the murine model of late infantile CLN2 disease (Chang et al 2008; Xu et al 2011). Encouragingly, intrathecal administration of recombinant TPP1 also reduces lysosomal storage in a large animal model (canine) of late infantile CLN2 disease (Vuillemenot et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, important concerns associated with gene therapy currently limit its clinical utility (19,20). Another approach is direct administration of enzyme into the cerebrospinal fluid (CSF) (21,22). Even though treated mice showed improvements in disease phenotypes, concerns remain whether such invasive methods are practical in humans.…”
mentioning
confidence: 99%